Leadership and the Research Productivity of University Departments - Amanda H. Goodall; John M. McDowell; Larry D. Singell (Institute for the Study of Labor (IZA), 2014)
Much of human knowledge is produced in the world's university departments. There is little scientific evidence, however, about how those hundreds of thousands of departments are best organized and led. This study hand-collects longitudinal data on departmental chairpersons in 58 US universities over a 15-year period. There is one robust predictor of a department's future research output. After adjustment for a range of personal and institutional characteristics, departmental research productivity improves when the incoming department Chair's publications are highly cited. A one SD increase in citations is associated with a 0.5 SD later rise in departmental productivity. By contrast, the quality-weighted publication record per se of the incoming Chair has no predictive power.
Keywords: I12; I23; M51; M54; 330; scientific productivity; department chairs; expert leaders